Tree bark as bioindicator of metal accumulation from road traffic and air quality map: A case study of Chiang Mai, Thailand - Rungruang Janta (2018)
© 2017 Turkish National Committee for Air Pollution Research and Control Trees have been recognized as air quality bioindicators, but they have still not been fully implemented in tropical areas. In this study, bark of Cassia fistula was used to inspect accumulation of air pollutants (metals) emitted from road traffic in the city of Chiang Mai, Thailand. The mean concentrations of metal accumulated on tree bark (ng/cm2) in descending order were Al (1,238) > Fe (707) > Zn (162) » Cu (21.1) » Pb (6.37) > Cr (2.14). Correlations of Enrichment Factors: EFTS(metal concentrations on bark compared to those in soil) among metals were relatively strong (r > 0.6) meaning that they were probably generated from the same sources. Moreover, principal component analysis and cluster analysis of EFTSvalues revealed that Al and Fe were generated from soil resuspension that were attached on vehicle wheels and on road surfaces, while Cr, Cu, Pb and Zn resulted directly from vehicle emissions. The results lead to the conclusion that tree bark is a good bioindicator for air pollutant accumulation in this area. In addition, pollution indices, including total geoaccumulation index (IGEO-tot) and pollution load index (PLI), were applied to generate air quality maps of the city. The maps illustrated that the most polluted areas in the city are the areas that have high traffic volume and building density, in which hospitals and schools are located. The degree of pollution presented in each area was influenced by both road traffic volume and density of buildings in relation to air ventilation capacity.